Doppler flowmetry in preeclampsia - Zahumensky, J (Bratislavske lekarske listy, 2009)
UNLABELLED: The purpose of this study was to summarize the new published data on the Doppler flowmetry in preeclampsia. METHODS: We summarize the new published data on the Doppler flowmetry in uteroplacental, fetoplacental and fetal circulation in preeclampsia. The present review summarized the results of clinical research on the Doppler flowmetry in the screening of risk of preclampsia, in the diagnosis of preclampsia and in the fetal risk in preclampsia (Ref. 19). Full Text (Free, PDF) www.bmj.sk.
Keywords: Blood Flow Velocity; těhotenství; Uterus; plod; uterus; Rheology; Placental Circulation; ultrasonografie; ženské pohlaví; Humans; Pregnancy; reologie; Ultrasonography; Fetus; rychlost toku krve; Female; placentární oběh; Pre-Eclampsia; preeklampsie; lidé